Determinant factors of psychological well-being and parental resilience in parents of children with cancer: A systematic review - Nurrohmah, Azizah; Chodidjah, Siti; Lestari, Ayu Widya; Huda, Mega Hasanul (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Childhood cancer remains a major global health concern, significantly impacting parents psychological well-being. A child’s cancer diagnosis often triggers emotional distress, anxiety, and long-term uncertainty for the family. Purpose: To identify the determinant factors of psychological well-being and parental resilience among parents of children with cancer. Method: Observational studies evaluating psychological well-being and resilience in parents of children with cancer were systematically searched in the databases PubMed, ScienceDirect, EBSCOhost, Sage Journals, and Scopus. Data were extracted independently by two reviewers. We included seven studies involving a total of 892 parents from various countries who have children with cancer. Results: Protective factors that were found to significantly enhance resilience and psychological well-being include spiritual well-being, social support, self-efficacy, and coping strategies. Conversely, psychological factors such as trauma, depression, anxiety, and general health status were significantly negatively correlated with both psychological well-being and resilience (p < 0.05). Conclusion: The reviewed studies consistently demonstrate that parental resilience and well-being are strongly influenced by spiritual well-being, social support, self-efficacy, and coping strategies. Negative psychological variables such as depression, anxiety, and trauma significantly contribute to the decline in psychological well-being and resilience.